Uji Total Flavonoid dan Aktivitas Antioksidan Fraksi Daun Brotowali sebagai Diabetes Ulkus - Jhon Evan Iskandar Manullang; Novitaria Br Sembiring; Astriani Natalia Br Ginting (Yayasan Literasi Sains Indonesia, 2026)
Diabetic ulcers are a chronic complication of diabetes mellitus characterized by impaired wound healing due to increased oxidative stress. One therapeutic approach that can be developed is the use of medicinal plants with antioxidant activity, such as Tinospora crispa leaves (Tinospora crispa), which contain flavonoids. This study aimed to determine the total flavonoid content and antioxidant activity of Tinospora crispa leaf fractions. Extraction was carried out using 96% ethanol, followed by fractionation using n-hexane, ethyl acetate, and water. Flavonoid content was determined using UV-Vis spectrophotometry using quercetin as a standard at a wavelength of 430.5 nm, while antioxidant activity was tested using the DPPH method. The results showed that the Tinospora crispa leaf aqueous fraction contained flavonoids of 0.2179 mg QE/g, with a linear calibration curve (R² = 0.997). Furthermore, the aqueous fraction demonstrated very strong antioxidant activity with an IC₅₀ value of ±16 µg/mL. Based on these results, the water fraction of brotowali leaves has the potential to be a source of natural antioxidants that can support the healing of diabetic ulcers by suppressing oxidative stress.